Paper title: A Study on English Speaking Skills among the University Students in South Libya (Journal of Human Sciences, 2021)
English is an international language and it has grabbed the status of a link language in the globalized scenario. This is the reason why, acquisition of English language skills, especially the speaking skills, has been considered one among the important skills to be obtained by the learners where English is not the learners' mother tongue. This paper studies the English language speaking skills among the university students in south Libya, particularly in and around Brack, Alshatti region. Studying the factors that hurdle the students' English speaking abilities has been the problem of the research. The objective of this paper is to present the level of the university students in English speaking skills in the region in their day to day communication and suggest effective ways to improve their skills thereby. This study is conducted at the Faculty of Education, Brack, Sebha University, Libya. The researcher, being an English lecturer at the same faculty for more than three years, assesses the English speaking skills of the students through thorough interactive observation on a regular basis while teaching in the class and lists out the beneficial ways that can boost the English oral skills of the students. Hence, the recommendations are made on the basis of the qualitative analysis of the researcher’s observations.